Pengaruh Temuan SPI, Temuan Kepatuhan, Tindak Lanjut Hasil Pemeriksaan dan Penyelesaian Kerugian Daerah Terhadap Opini Audit di Kabupaten/Kota Provinsi Sumatera Selatan - Jessica Valentina Valentina (Syntax Idea, 2022)
This study aims to determine the effect of SPI findings, compliance findings, follow-up inspection results and settlement of regional losses on audit opinions in districts/cities of South Sumatra province. The type of research used in this research is quantitative research using secondary data obtained from the official website www.bpk.go.id and requests for data on inspection reports to the BPK RI head office. The population used in this study were all districts/cities in the province of South Sumatra, namely 17 districts/cities with a total of 85 samples. The sample selection used the saturated sample method, which is a sampling technique when all members of the population are used as samples. Testing this hypothesis using Logistic Regression analysis with T test, F test, and the coefficient of determination. The data were analyzed with the help of SPSS version 26 software. The results of this study indicate that partially the Compliance Findings have a negative and significant effect on Audit Opinion. Meanwhile the SPI Findings, Follow Up on Audit Results and Settlement of Regional Losses have no and no significant effect on the Audit Opinion. Simultaneously SPI Findings, Compliance Findings, Follow-up on Examination Results and Settlement of Regional Losses have a positive and significant impact on Audit Opinion in the Regency/City of South Sumatra Province.